2011
DOI: 10.3389/fnana.2011.00021
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Dopamine Systems in Chordates

Abstract: Dopamine (DA) neurotransmission in the central nervous system (CNS) is found throughout chordates, and its emergence predates the divergence of chordates. Many of the molecular components of DA systems, such as biosynthetic enzymes, transporters, and receptors, are shared with those of other monoamine systems, suggesting the common origin of these systems. In the mammalian CNS, the DA neurotransmitter systems are diversified and serve for visual and olfactory perception, sensory–motor programming, motivation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
214
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(220 citation statements)
references
References 187 publications
6
214
0
Order By: Relevance
“…In contrast, in rats, one remarkable aspect of our findings is that the vast majority of the DA neurons that project to the striatum also project to the MLR, implying a simultaneous ascending and descending modulation of the entire locomotor command circuitry from cortex to brainstem. These DA neurons are mostly located in the SNc with a few in the RRF, two structures that are classically considered as mesencephalic but that also span in the diencephalon (16,19,20). In lampreys, the terminology "mesodiencephalic DA neurons" does not apply, given that the DA neurons are all located in the diencephalon (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in rats, one remarkable aspect of our findings is that the vast majority of the DA neurons that project to the striatum also project to the MLR, implying a simultaneous ascending and descending modulation of the entire locomotor command circuitry from cortex to brainstem. These DA neurons are mostly located in the SNc with a few in the RRF, two structures that are classically considered as mesencephalic but that also span in the diencephalon (16,19,20). In lampreys, the terminology "mesodiencephalic DA neurons" does not apply, given that the DA neurons are all located in the diencephalon (40).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of authors seem to agree with the hypothesis that at least some of the mesodiencephalic DA neurons located in the diencephalon are homologous in all vertebrates, and thus, homologous to at least a portion of the mammalian substantia nigra pars compacta (SNc)/ ventral tegmental area (VTA) (13,(15)(16)(17)(18)(19); for review, see ref. 20). Alternatively, it was suggested that the posterior tuberculum DA neurons projecting to the striatum in zebrafish are homologs of the mammalian DA neurons of the A11 group (21).…”
mentioning
confidence: 99%
“…As described above, important neuroanatomical (absence of the A9/mesolimbic projection) and genomic (duplication of tyrosine hydroxilase and of some receptors) differences exist between teleosts and mammals, and many of these differences are plesiomorphic in Gnathostomata (Yamamoto & Vernier, 2011). Some roles for dopamine receptors have been described in zebrafish defensive behaviour.…”
Section: Dopamine and The Aversive Behaviour Network Of Zebrafishmentioning
confidence: 99%
“…Dopamine is a key neurotransmitter involved in many different metabolic pathways and, more importantly, it serves as a neurohormone in arthropods [20]. It is known to be an important signalling molecule in various metabolic pathways in invertebrates (reviewed in [20]).…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine is a key neurotransmitter involved in many different metabolic pathways and, more importantly, it serves as a neurohormone in arthropods [20]. It is known to be an important signalling molecule in various metabolic pathways in invertebrates (reviewed in [20]). In fact, dopamine can regulate the synthesis and degradation of juvenile hormones [21,22], and thereby we hypothesized that it has the potential to control predatorinduced polyphenism.…”
Section: Introductionmentioning
confidence: 99%